Quantifying the relationship between symptoms at presentation and the prognosis of sarcoidosis. (June 2019) - Judson, Marc A.; Preston, Sara; Hu, Kurt; Zhang, Robert; Jou, Stephanie; Modi, Aakash; Sukhu, Indrawattie; Ilyas, Furqan; Rosoklija, Gavril; Yucel, Recai
Abstract: Background: Although it is the general consensus that sarcoidosis patients who present with sarcoidosis-related symptoms have a worse outcome than patients whose disease is detected incidentally without symptoms, this premise has not been rigorously examined. Methods: Consecutive patients followed longitudinally at one US university sarcoidosis clinic were questioned concerning the onset and description of sarcoidosis-related symptoms at disease presentation. The patients were classified into those with no sarcoidosis-related symptoms at presentation (NSP group) and those with symptoms at presentation (SP group). The following outcomes were examined in the NSP and SP groups: most recent spirometry, organ involvement, need for sarcoidosis therapy, most recent health related quality of life (HRQOL) as measured by the Sarcoidosis Assessment Tool (SAT), most recent chest imaging Scadding stage results. Results: 660 sarcoidosis patients were analyzed, with 175 in the NSP group and 485 in the SP group. Compared to the NSP group, the SP group had a more frequent requirement for any sarcoidosis treatment, corticosteroid treatment, and non-corticosteroid treatment at some time and within the most recent year of follow up (at least 50% more than the NP group with strong statistical differences with p values all 0.01 or less). In addition, the SP group had significantly more organ involvement (p < 0.001) and several worse SAT domains (p < 0.022) than the NP group. There were no differences between the groups in terms of final spirometry or development of Scadding stage 4 chest radiographs. These findings held even after adjusting for age, sex, race, and time between presentation and the most recent follow-up visit using a multivariable logistic regression framework. Conclusions: In our sarcoidosis cohort, compared to the absence of symptoms at presentation, the presence of symptoms was associated with a greater need for treatment, more organ involvement, and worse HRQOL.